Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1038/79194
|View full text |Cite
|
Sign up to set email alerts
|

In vivo selection using a cell-growth switch

Abstract: A major obstacle to stem-cell gene therapy rests in the inability to deliver a gene into a therapeutically relevant fraction of stem cells. One way to circumvent this obstacle is to use selection. Vectors containing two linked genes serve as the basis for selection, with one gene encoding a selectable product and the other, a therapeutic protein. Applying selection in vivo has the potential to bring a minor population of genetically corrected cells into the therapeutic range. But strategies for achieving in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 15 publications
2
104
0
2
Order By: Relevance
“…Thus, the dimerizer drug AP20187 did not appear to be toxic to control HDMECs, in agreement with a report that described low or no cytotoxicity of the drug to other cell types. 22 As low as 0.01 nM of AP20187 induced significant apoptosis and the level of apoptosis plateaued with 1 nM of the drug (Figure 2b). Under all conditions examined, induction of apoptosis in HDMECs was dependent on the addition of AP20187 and the expression of chimeric F v 2-caspase-9.…”
Section: Activation Of Caspase-9 Is Sufficient To Induce Endothelial mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the dimerizer drug AP20187 did not appear to be toxic to control HDMECs, in agreement with a report that described low or no cytotoxicity of the drug to other cell types. 22 As low as 0.01 nM of AP20187 induced significant apoptosis and the level of apoptosis plateaued with 1 nM of the drug (Figure 2b). Under all conditions examined, induction of apoptosis in HDMECs was dependent on the addition of AP20187 and the expression of chimeric F v 2-caspase-9.…”
Section: Activation Of Caspase-9 Is Sufficient To Induce Endothelial mentioning
confidence: 94%
“…The modified procaspase-9 mol- 19,22 We infected human dermal microvascular endothelial cells (HDMECs) with the iCaspase-9 retrovirus or control viruses and selected cell pools for a minimum of 2 weeks in the presence of G418. Immunoblotting with anti-caspase-9 antibody revealed that HDMECs transduced with the iCaspase-9 vector, but not with control retrovirus, expressed the chimeric iCaspase-9 protein (Figure 1b).…”
Section: Ap20187 Induces Activation Of Icaspase-9 In Microvascular Enmentioning
confidence: 99%
“…Moreover, the use of mutagenic selective agents generates formal problems in the interpretation of the results achieved. The other procedures used for in vivo selection either generated an inconsistent and unstable chimerism 10,24 or were associated with polyclonal expansion mediated by an overexpressed transcription factor that by itself could have an impact on transgene expression. 25 The present study demonstrates that single HSCs expressing the transgene in vivo from a retroviral vector introduced at a low copy number can give rise to serial repopulation with persisting expression in diverse multipotent, myeloid, lymphoid, erythroid and megakaryocytic lineages.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Selecting HSCs with active transgene expression in vivo would circumvent these problems only when the HSCs expressing the transgene at the time of selection would continue to do so in the absence of selection and through subsequent clonal amplification and differentiation. Selection procedures applicable in vivo are based on the transfer and expression of genes mediating resistance to cytotoxic drugs, 3,[20][21][22][23] encoding artifical signal transfer molecules, 24 or providing an inherent growth advantage. 25 If operative at the level of the HSCs and applied with high stringency, these selection procedures should result in completely transgenic hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…21 Successful in vivo expansion of gene-modified hematopoietic cells was obtained using the cell growth switch composed of the intracellular part of Mpl and FKBP in a murine model. 22 We previously developed a chimeric selective amplifier gene (SAG) composed of the signalling domain of the granulocyte colony-stimulating factor (G-CSF) receptor and the estrogen receptor hormone-binding domain, and demonstrated that primary bone marrow progenitor cells transduced with the SAG could be expanded in response to estrogen or tamoxifen in vitro. 18,23,24 The estrogen receptor-mediated dimerization of the chimeric gene product is assumed to be critical for the activation of the G-CSF receptor signaling.…”
Section: Encoding the Sag And Reinfused Into Each Myeloablated Monkeymentioning
confidence: 99%